Feasibility and acceptability of reducing workplace sitting time: a qualitative study with Australian office workers. (December 2016) - Hadgraft, Nyssa; Brakenridge, Charlotte; LaMontagne, Anthony; Fjeldsoe, Brianna; Lynch, Brigid; Dunstan, David; Owen, Neville; Healy, Genevieve; Lawler, Sheleigh
Abstract Background Office workers spend a large proportion of their working hours sitting. This may contribute to an increased risk of chronic disease and premature mortality. While there is growing interest in workplace interventions targeting prolonged sitting, few qualitative studies have explored workers' perceptions of reducing occupational sitting outside of an intervention context. This study explored barriers to reducing office workplace sitting, and the feasibility and acceptability of strategies targeting prolonged sitting in this context. Methods Semi-structured interviews were conducted with a convenience sample of 20 office workers (50 % women), including employees and managers, in Melbourne, Australia. The three organisations (two large, and one small organisation) were from retail, health and IT industries and had not implemented any formalised approaches to sitting reduction. Questions covered barriers to reducing sitting, the feasibility of potential strategies aimed at reducing sitting, and perceived effects on productivity. Interviews were audiotaped and transcribed verbatim. Data were analysed using thematic analysis. Results Participants reported spending most (median: 7.2 h) of their working hours sitting. The nature of computer-based work and exposure to furniture designed for a seated posture were considered to be the main factors influencing sitting time. Low cost strategies, such as standing meetings and in-person communication, were identified as feasible ways to reduce sitting time and were also perceived to have potential productivity benefits. However, social norms around appropriate workplace behaviour and workload pressures were perceived to be barriers to uptake of these strategies. The cost implications of height-adjustable workstations influenced perceptions of feasibility. Managers noted the need for an evidence-based business case supporting action on prolonged sitting, particularly in the context of limited resources and competing workplace health priorities. Conclusions While a number of low-cost approaches to reduce workplace sitting are perceived to be feasible and acceptable in the office workplace, factors such as work demands and the organisational social context may still act as barriers to greater uptake. Building a supportive organisational culture and raising awareness of the adverse health effects of prolonged sitting may be important for improving individual-level and organisational-level motivation for change.